Pulmonary Sequestration: Early Diagnosis and Management - Sajad A. Wani; Gowher N. Mufti; Nisar A. Bhat; Ajaz A. Baba (Case Reports in Pediatrics)
Intralobar sequestration is characterized by aberrant formation of nonfunctional lung tissue that has no communication with the bronchial tree and receives systemic arterial blood supply. Failure of earlier diagnosis can lead to recurrent pneumonia, failure to thrive, multiple hospital admissions, and more morbidity. The aim of this case report is to increase the awareness about the lung sequestration, to diagnose and treat it early, so that it is resected before repeated infection, and prevent the morbidity and mortality.